Mycotoxin profiles of solar tent-dried and open sun-dried plantain chips - Adenitan, A.A.; Awoyale, W.; Akinwande, B.A.; Maziya-Dixon, Busie; Michael, S. (Elsevier, 2021)
Plantain is a popular dietary staple in Central and West African countries due to its versatility and excellent nutritional value. Mature unripe plantain finger is usually processed into dried chips by processors using open sun-drying method to reduce the moisture content and extends its shelf life, but without controlling the unit operations that affect product quality. Thus, this study aimed at assessing the mycotoxin profile of solar tent-dried and open sun-dried plantain chips in Nigeria. Fifty (50) dried plantain chips [10 samples produced from the solar tent-dried, 10 samples from open sun dried, and 30 samples from local processors (9 from Akure South and 21 from Idanre Local Governments)] were analyzed for constituent mycotoxins using Liquid Chromatography Tandem-Mass Spectrometry (LC-MS/MS). The result reveals that all the regulated mycotoxins (Aflatoxin B1, B2, G1, G2, Ochratoxin A, Fumonisin B1, Fumonisin B2, Zearalenone, T-2 Toxin, HT-2 Toxin and, Deoxynivalenol) were below the detectable limits in the dried plantain chips. Aflatoxin B1 and G1, which were considered as the most regulated mycotoxin, were below the limits of detection (0.16–0.22 μg/kg) in all the samples. Only 23 analytes were detected at concentrations higher than their respective limits of detection (LOD) in 2% or more of the 50 dried plantain chips investigated, with reference to the prevalence of the non-regulated mycotoxins. Thus, all regulated mycotoxins produced by Aspergillus, Penicillium and Fusarium as stipulated by the Commission of the European Union were found at concentrations which are toxicologically acceptable in many other crops, particularly in the solar tent-dried plantain chips compared to those from the open sun-dried and local processors. Therefore, the use of a solar tent in drying plantain chips and other agricultural products is encouraged for the safety of human consumption. The outcome of this study provides useful information regarding the possible safety of plantain chips in Nigeria.